Psychometric properties of the diabetes skills checklist for adolescents with type 1 diabetes and their parents. Issue 6 (13th July 2021) - Papadakis, Jaclyn Lennon; Shapiro, Jenna B.; Evans, Meredyth; Feldman, Marissa A.; Weil, Lindsey E. G.; Vesco, Anthony T.; Thompson, Laurie Gayes; Garza, Kimberly; Weissberg‐Benchell, Jill
Abstract: Objective: Among adolescents with type 1 diabetes, research has found that their perception of their diabetes management is an important predictor of actual diabetes management. There is a need for measures that assess adolescents' perception of their ability to independently complete daily diabetes self‐care tasks. The current study examined the psychometric properties of the Diabetes Skills Checklist Teen‐Report (DSC‐T) and DSC Parent of Teen‐Report (DSC‐PT), which assess perceived independence in diabetes self‐care skills. Research Design and Methods: Data were from 1450 adolescents aged 12 to 18 years and their parents who participated in the Diabetes Camp Matters Study. Families completed the DSC as well as other questionnaires online assessing demographic and diabetes‐related information, diabetes strengths, and diabetes‐specific emotional distress. Results: Exploratory factor analysis revealed a 14‐item DSC‐T and 12‐item DSC‐PT, both with excellent internal consistency and concurrent validity. Both the DSC‐T and DSC‐PT were found to be positively correlated with diabetes strengths and negatively correlated with HbA1c, and the DSC‐PT was significantly correlated with parent‐reported diabetes distress. Adolescents who used insulin pumps and continuous glucose monitoring reported higher perceived independence in diabetes self‐care skills compared to adolescents who used insulin pens/syringes or blood glucose meters. No differences were found based on demographic characteristics. Conclusions: The DSC‐T and DSC‐PT have strong potential to be used during diabetes clinic visits to spark discussion regarding adolescents' self‐care, which would allow for a more successful transfer of diabetes care from parent to adolescent, and eventually, the transition from pediatric to adult healthcare.